2014
DOI: 10.1177/155892501400900206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Woven Denim Fabric Sewability based on Needle Penetration Force

Abstract: This paper investigates the sewability of the woven denim fabrics based on needle penetration force (NPF). For this purpose, the effects of fabric weight, number of fabric layers, needle size, and the interaction effect of these parameters on NPF in twill denim fabrics were investigated. In addition, the influence of weave pattern on NPF was studied. The statistical analysis results show that NPF is influenced by these parameters. Fabric weight has a greater effect on NPF than other parameters. With increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…The results presented are consistent with previous work [12,17,18], with the exception of peak 2 with material B. Still, the general trend is a clear increase in needle penetration force with needle size.…”
Section: Effect Of Needle Size On Needle Penetration Forcessupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented are consistent with previous work [12,17,18], with the exception of peak 2 with material B. Still, the general trend is a clear increase in needle penetration force with needle size.…”
Section: Effect Of Needle Size On Needle Penetration Forcessupporting
confidence: 92%
“…Finally, another method for measurement of needle penetration forces was proposed by Haghighat, Etrati, and Najar [18]. In this case, an Instron 5566 Tensile Tester is used.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Previous studies showed that seam appearance and performance depend on the interrelationship of fabrics, threads, stitch types and sewing conditions [16,17,18] According to the newly development processes in clothing industry, particularly in denim garment, the seam performance of denim is important. In the sewing process, a fabric with high density, thickness and weight such as denim fabric is more phone to seam and stitch damages [19]. Breaking strength and elongation of the fabric and sewing thread had an excellent correlation with seam efficiency [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand if polyester percentage is more in fabric show less resistance during sewing operation. However, the linear density of sewing thread shows insignificant effect on seam stiffness [12,24]. Different blended fabrics show significant effect on drape coefficient.…”
Section: Influence Of Fabric Parameters On Seam Qualitymentioning
confidence: 96%
“…The appearance of a seam is generally lead by the proper relationship between the size and type of thread, the stitch density and its types, and the texture and weight of the fabric [11]. Many researchers found that fabric quality parameters, such as fabric density, fabric thickness, tensile strength, extensibility, bending rigidity, and shear rigidity have extreme effect on quality of seam [12]. Different researcher gives a subjective ranking for evaluation of seam performance [13].…”
Section: Introductionmentioning
confidence: 99%